Can WhatsApp Enhance Students' Learning in CLIL? - Lara Martínez; Delicia Fernández Medina; Cecilia Zabala (Universidad de La Sabana, 2023)
The aim of this paper is to show the impact of Information and Communications Technology (ICT) by using WhatsApp with activities based on collaborative work, real time communication, and feedback. The relevance of presenting authentic material such as topics of students' interest combined with collaborative work is central for developing motivation and success within the Content and Language Integrated Learning (CLIL) approach. The paper describes two activities: The first activity focuses on the creation of sentences using Google Photos, and the second one focuses on listening and speaking skills by using the shared space facilitated through WhatsApp as a mediation resource used by teachers in their classrooms, among other 21st-century digital tools. Also, the objective of achieving optimal learning outcomes promotes the increase of educational quality.